Economic assessment and prospect of hydrogen generated by OTEC as future fuel. (5th January 2017) - Banerjee, Subhashish; Musa, Md. Nor.; Jaafar, Abu Bakar
Abstract: Hydrogen used for production of electricity through electrolysis using renewable energy systems is a costlier proposition. To date 96% of hydrogen production occurs from steam reformation of fossil fuels. Water splitting method from high temperature cracking, photo electrolysis, or biological decomposition processes, are in the research stage. Life cycle cost analysis on hydrogen economy as transport fuel with fuel cell combine, including resolving its storage and transportation problems with cost of hydrogen production from power generated using different types of Ocean Thermal Energy Conversion (OTEC) plants, are evaluated. Scope of availability of hydrogen refuelling station from 100 MW (net power) OTEC plant could be determined. Advancement in OTEC technology could help in developing 2nd/3rd generation plants (using solar hybrid OTEC; Uehara cycle). The scope of by-product availability can make its electricity production cost much cheaper and would make a viable proposition in producing OTEC powered hydrogen. This is suggested to resolve the challenges in hydrogen production economy. Highlights: OTEC driven hydrogen plants, may meet the challenges in improving hydrogen economy. 2nd/3rd generation OTEC plants with available by-products reduce electricity cost. CH3 OH and/or NH3 production from H2 may resolve storage and transport issues of H2 . Improvement in fuel cell technology may help use of H2 as transport fuel. R&D of H2 generated by photoelectrolysis & biological processes have future promise.